International Law: A Discipline of Crisis - Charlesworth, Hilary (Res Severa Verum Gaudium, 2025)
This article examines the way that international lawyers tend to focus on crises for the development of international law. It uses the reactions of international lawyers to NATO’s intervention in Kosovo in 1999 as a case study of this tendency and argues that the crisis focus impoverishes the discipline of international law. The article proposes the idea of an international law of everyday life as an alternative.